Associations Between Mental Health Problems in Adolescence and Educational Attainment in Early Adulthood: Results of the German Longitudinal BELLA Study - Meißner, Carina; Meyrose, Ann-Katrin; Kaman, Anne; Michalkiewicz, Martha; Ravens-Sieberer, Ulrike (Frontiers in Pediatrics, 2022)
Mental health problems (MHP) in adolescence are a major public health concern of the 21st century. Global prevalence estimates range between 10 and 20%. Most MHP manifest by adolescence and persistence rates are high, often accumulating further impairment in early adulthood and beyond. We analyzed data of N = 433 participants from the German longitudinal BELLA study to examine whether MHP in adolescence negatively affect educational attainment in early adulthood. Externalizing and internalizing MHP among adolescents aged 11–17 years were assessed at baseline using the Strengths and Difficulties Questionnaire. Educational attainment was assessed at the 6-year follow-up based on level of education, failure to attain the expected level of education, and dropout from vocational or academic training. Findings from logistic regression analyses suggest that more pronounced externalizing MHP in adolescence predict a lower level of education in early adulthood. We did not find a corresponding effect for internalizing MHP. Adolescents with higher-educated parents were less likely to attain a lower level of education themselves and less likely to fail in attaining their expected level of education. Our findings support that educational attainment presents a central channel for intergenerational reproduction of education and forms an important pathway for upward, but also downward social mobility. The current study emphasizes school as a central setting to implement measures to prevent onset and persistence of MHP and to foster equal opportunities in education.